Edukasi dan Pendampingan Edukasi Tanaman Bernilai Ekonomi Tinggi Pada Masyarakat di Madyapuro Melalui Budidaya Bonsai - Sulistyono, Setyo Wahyu; Anindyntha, Firdha Aksari (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
The economic sector is faced with many problems due to Covid-19. One of that is declining in economic activity which has a direct impact on the household economy, thus leading to efforts to create new economic activities in society. Dongkel is a depletion activity that aside the ecosystem to obtain economic benefits. This must be reduced through the conversion of activities in the community through an economic value approach and business management. This community service program seeks to provide public awareness of dongkel cultural activities which tend to be passive in terms of social and environmental economic values. The first step in implementing this program is giving education about the dangers of depletion for socio-economic life and the environment. Second, by encouraging the community in the RW 004 area of Madyapuro District to initiate the conversion of dongkel activities into cultivating plants with high economic value, namely bonsai. Third, by holding bonsai training as an activity to support household economic activities in the community. Fourth, by providing digital marketing training to sell the bonsai plant products. Hopefully, the result of this program is the establishment of public awareness in the cultivation of bonsai plants as a momentum to increase nature conservation and also the community's economy in era pandemic.